2021
DOI: 10.1002/ejhf.2287
|View full text |Cite
|
Sign up to set email alerts
|

Stopping mineralocorticoid receptor antagonists after hyperkalaemia: trial emulation in data from routine care

Abstract: Whether to continue or stop mineralocorticoid receptor antagonists (MRA) after an episode of hyperkalaemia is a challenge in clinical practice. While stopping MRA may prevent recurrent hyperkalaemias, it deprives patients of their cardioprotection. We here assessed the association between stopping vs. continuing MRA therapy after hyperkalaemia and the subsequent risks of adverse health events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…We appreciated the comments by Alexandrou and Sarafidis on our study about the clinical consequences of stopping versus continuing mineralocorticoid receptor antagonist (MRA) treatment after hyperkalaemia. 1 We observed that stopping MRAs, compared with continuing, was associated with a higher risk of mortality. In stratified analyses, there were similar effects among patients with estimated glomerular filtration rate <60 or ≥ 60 ml/min/1.73 m 2 , with hazard ratios of 1.20 (95% confidence interval [CI] 1.09-1.33) and 1.08 (95% CI 1.01-1.15) respectively, that indicates lack of heterogeneity across strata.…”
Section: Reply To the Letter Regarding The Article 'Stopping Mineralo...mentioning
confidence: 76%
“…We appreciated the comments by Alexandrou and Sarafidis on our study about the clinical consequences of stopping versus continuing mineralocorticoid receptor antagonist (MRA) treatment after hyperkalaemia. 1 We observed that stopping MRAs, compared with continuing, was associated with a higher risk of mortality. In stratified analyses, there were similar effects among patients with estimated glomerular filtration rate <60 or ≥ 60 ml/min/1.73 m 2 , with hazard ratios of 1.20 (95% confidence interval [CI] 1.09-1.33) and 1.08 (95% CI 1.01-1.15) respectively, that indicates lack of heterogeneity across strata.…”
Section: Reply To the Letter Regarding The Article 'Stopping Mineralo...mentioning
confidence: 76%
“…Trevisan et al. [65] employed target trial emulation methods based on cloning, censoring and weighting to evaluate the decision to stop or to continue MRA after an episode of hyperkalaemia. Although stopping MRAs is a common practice to prevent recurrent hyperkalaemia, it may have undesirable consequences as it deprives patients of their needed cardioprotection.…”
Section: Key Findings Of Screammentioning
confidence: 99%
“…Trevisan et al [65]. employed target trial emulation methods based on cloning, censoring and weighting to evaluate the decision to stop or to continue MRA after an episode of hyperkalaemia.…”
mentioning
confidence: 99%
“…We read with interest the article of Trevisan et al, 1 reporting an 11% higher 2-year risk for death after discontinuation of mineralocorticoid receptor antagonists (MRA) due to a hyperkalaemia episode, a reduction that was consistent across estimated glomerular filtration rate (eGFR) strata, according to authors. Although limited by its observational nature, the study has many strengths including a large population mirroring routine clinical practice and a rigorous analysis.…”
Section: Letter Regarding the Article 'Stopping Mineralocorticoid Rec...mentioning
confidence: 99%